Forty Years of Archaeological Research along the Omani Shores of the Arabian Sea - Charpentier, Vincent; Maiorano, Maria Pia; Borgi, Federico; Vosges, Jérémie (First International Conference on the Archaeology of the Oman Peninsula, 2026)
Research conducted along the Omani coastline of the Arabian Sea has revealed a new chapter in the history of early maritime communities. Globally, most coastal habitats from the early Holocene have been submerged by rising sea levels. The caves in the cliffs of Natif (Hasik, Dhofar) are an exception in Arabia: they are currently the only evidence of maritime communities from the Late Paleolithic period on the peninsula. Between the early 9th and 8th millennia BCE, these early Arabian fishermen focused on catching small pelagic species (anchovies and sardinella), as well as rays and sharks. Around 6000 BCE, the shores of the Arabian Peninsula were covered with Neolithic settlements, sometimes consisting of large shell middens. The mission discovered a large number of these along the Arabian Sea and explored several, notably at Suwayh, Ruwayz, Khuwaymah, Masirah Island, Sharbithat, Hasik, Ad Dahariz, Hallaniyah Island, etc. Among these, the Suwayh SWY-1 settlement is particularly noteworthy, as its inhabitants specialized in shark fishing between 5800 and 4400 BCE. This Neolithic period also saw the conquest of island environments, including the large island of Masirah and the Hallaniyat archipelago. While Masirah was occupied early on (5900-5600 BCE), Hallaniyah was settled much later (around 4400 BCE). By this time, the entire territory of Oman had been conquered by Neolithic communities. At the same time, the mission worked to establish a chronology for these periods. In Sharbithat Bay, as in Hasik, it is currently bringing to light a new facies from the very end of the Neolithic period, between 3700 and 3100 BCE.